Adequacy and accuracy of nontrauma center computed tomography: What are we missing?. Issue 1 (July 2017) - Bonds, Morgan Michelle; Hersperger, Stephen; Garwe, Tabitha; Fails, Robert; Johannesen, Sigrid; Kim, Christina; Adeseye, Ademola; Lees, Jason; Havron, William
Abstract : BACKGROUND: Timely and appropriate use of computed tomography (CT) scans is critical to the evaluation of traumatic injuries. The objective of this study was to assess the adequacy of CT scans performed at nontrauma centers (NTCs) as they pertain to the management of trauma patients. METHODS: Adult patients transferred to our ACS-verified Level I trauma center from any NTC between May and December 2012 were enrolled prospectively. Available CT images from NTCs were reviewed in a blinded fashion by our facility's trauma radiologist; his interpretations were compared with those from the NTC. Interpretations of the trauma centers (TCs) images were compared with the NTC interpretations. Means and proportions were used to summarize the data. RESULTS: A total of 235 consecutive patients with a complete dataset were included, of which, 203 (86.4%) had a CT scan performed at an NTC. Additional imaging was obtained at the TC in 76% of patients with outside CT (154 of 203), with inadequacy of outside CTs for patient workup based on mechanism of injury (76%) and technical inadequacy of outside images (31%) being the main, nonexclusive reasons to repeat imaging. Image interpretation by the trauma radiologist at the TC using NTC images identified missed injuries in 49% of the patients, and 90% of these missed injuries were deemed clinically significant, meaning the injury would have altered patient care had they been identified. When the same body region was imaged at the TC, 54% had missed injuries, of which 76% were deemed significant. CONCLUSION: This study demonstrates inaccuracy in the interpretation of NTC images, which can lead to inappropriate management of trauma patients. Parameters other than imaging need to be used to identify patients requiring a higher level of care. LEVEL OF EVIDENCE: Therapeutic and care management study, level V.